MODEL AND INDIVIDUAL QUALITY METRICS OF SCIENTIFIC PUBLICATIONS - Subbotin, S. A. (Radio Electronics, Computer Science, Control, 2015)
The existent metrics of scientific publications has been analyzed. Their common disadvantage is the external evaluation of articles relatively to external level to their content. This obviously does not allow to assess the quality of presentation of the article. The purpose of this paper is to develop a set of indicators to characterize the properties of scientific papers in terms of their structure, vocabulary and forms of presentation, as well as a bibliography. The set of metrics allowing to quantificate the material individual properties and to automate the analysis of scientific publications has been defined. The proposed set includes such paper indices as: potential readership coverage, structuring, diversity of geography, languages and types of bibliographic sources, bibliography quality, text richness by the links to sources, figures and tables number and quotability, Illustrativity, mathematical apparatus volume and the use, abbreviation effectiveness, paper vocabulary indices (compliance of title with text, of title with author’s abstracts, of author’s abstracts with text, of keywords with abstracts, of keywords with title, of keywords with text, of keywords with characteristic words, of abstracts with characteristic words, of names with characteristic words, of UDC with paper vocabulary, of tables and figures descriptions with text, of vocabulary compliance with paragraphs, of references names with text), self-citations of the authors, author team quality, hybrid and integrated indicators of paper quality. The examples confirming practical applicability of the proposed indicators are shown.